Upaya Peningkatan Kemampuan Literasi pada Anak Usia 4 – 5 Tahun Melalui Kartu Bergambar di PAUD El-Elly Bangsalsari Jember - Alifa, Hilmiyah; Zahro, Ianatuz; Kuswardani, Herini (Efektor, 2024)
The aim of this research is to use picture cards to improve the literacy skills of children aged 4 - 5 years at PAUD El-Elly Bangsalsari Jember in the 2023-2024 school year. This research uses Classroom Action Research (PTK). This method combines two learning cycles: planning, implementing, observing, and reflecting. Qualitative and quantitative analysis is used. The research results showed that children's literacy skills increased significantly when the learning methods in cycle II were improved. In Cycle I, 50% (7 students) completed the Developing According to Expectations (BSH) and Very Well Developing (BSB) categories. Increased in Cycle II, with 85% (12 students) completing the same category. The results show that picture cards can foster children's interest and literacy skills and help them understand the relationship between pictures, letters and words. This shows that the use of creative and flexible learning media in early childhood education is very important to optimize children's literacy development.